Effect of s.a.q training on certain physical variables and performance level for sabre fencers - Mohamed, S. A.; Larion, A. (Science, Movement & Health, 2018)
Aim. Speed, Agility and Quickness (SAQ) training has become a very popular method for training athletes. Any athlete, from a child to a professional player, can benefit from it. This method has been implemented for several years, but still today is not used by some athletes mainly due to the lack of knowledge about the type of maneuvers to be used. This type of training can be used to increase the speed and the capacity to develop maximum force during movements at high speeds, since it manipulates and takes better advantage of the stretch-contraction cycle of the muscle, thus reducing the gap that exists between training Traditional resistance and functional training with specific movements. The purpose of this study was to investigate the effect of S.A.Q training on certain physical variables and performance level for sabre fencers. Methods. The sample comprised random from elite fencers in Egyptian fencing club. (20) fencers, the subjects divided into two groups. The experimental group (n= 10) participated in S.A.Q training program four- times weekly, Ten weeks. The control group (n= 10) participated in the traditional program for the same period. Results. Significant Difference between the experimental group and control group in certain physical variables (Leg strength, Back strength, Coordination, Agility, movement speed and performance level) for the experimental group. Conclusions. Finally, the findings indicated that the S.A.Q training program for ten weeks could improvement the physical variables (Leg strength, Back strength, Coordination, Agility, movement speed and performance level) for the experimental group. These results have to be taken into account by Trainers in order to better understand and implicated of these concepts in training sessions and lessons.